Pd and Re isotope production in the field of mixed X,n-radiation of electron accelerator - Dikiy, N.P.; Kushnir, V.A.; Lyashko, Yu.V.; Mitrochenko, V.V.; Perezhogin, S.A.; Rogov, Yu.V.; Tenishev, A.Eh.; Torgovkin, A.V.; Uvarov, V.L.; Shevchenko, V.A.; Shlyakhov, I.N.; Shramenko, B.I. (Вопросы атомной науки и техники, 2013)
Radioactive isotopes of palladium (¹⁰³Pd) and rhenium (¹⁸⁶Re and ¹⁸⁸Re) have found wide use in nuclear medicine. The present report deals with the conditions for their production by a photonuclear method at an electron accelerator. Studies have been made into the channels of target isotope/attendant impurity production as palladium and rhenium targets of natural isotopic composition were exposed to a mixed flux of X-ray (bremsstrahlung) with end-point energy of 40 MeV and photoneutrons. By placing a bremsstrahlung converter and the target inside a neutron moderator, data have been obtained for the effect of photoneutron spectrum on the isotope yield. The simulation technique has been used to investigate the photonuclear yield of target isotopes and major impurities as function of electron energy. Радіоактивні ізотопи паладію (¹⁰³Pd) та ренію (¹⁸⁶Re і ¹⁸⁸Re) широко використовуються в ядерній медицині. Вивчаються умови їх отримання фотоядерним методом на прискорювачі електронів. Досліджено канали напрацювання цільових ізотопів і домішок при опромінюванні мішеней з паладію і ренію природного ізотопного складу змішаним потоком гальмівного випромінювання з граничною енергією 40 МеВ і фотонейтронів. Шляхом розміщення конвертера гальмівного випромінювання і мішені усередині модератора нейтронів отримано дані щодо впливу спектра фотонейтронів на вихід ізотопів. Методом моделювання вивчена також залежність фотоядерного виходу цільових ізотопів і основних домішок від енергії електронів. Радиоактивные изотопы палладия (¹⁰³Pd) и рения (¹⁸⁶Re и ¹⁸⁸Re) широко используются в ядерной медицине. Изучаются условия их получения фотоядерным методом на ускорителе электронов. Исследованы каналы наработки целевых изотопов и примесей при облучении мишеней из палладия и рения природного изотопного состава смешанным потоком тормозного излучения с граничной энергией 40 МэВ и фотонейтронов. Путем размещения конвертера тормозного излучения и мишени внутри модератора нейтронов получены данные по влиянию спектра фотонейтронов на выход изотопов. Методом моделирования изучена также зависимость фотоядерного выхода целевых изотопов и основных примесей от энергии электронов.